High seroprevalence of Rickettsia spp. and molecular detection of Rickettsia amblyommatis in human-biting ticks from the eastern Amazon, Brazil - Mayra F. F. R. Ferreira; Lina de Campos Binder; Rafael M. S. Nogueira; Ruth M. M. e Silva; Carlos C. M. Ramos; Leonardo T. Dall’Agnol; Thiago Fernandes Martins; Raphaela B. M. Bittencourt; Felipe da Silva Krawczak; Livio Martins Costa-Junior; Marcelo Bahia Labruna; Mayara I. S. Lima; et al. (Parasites & Vectors)
Abstract Background In Brazil, spotted fever (SF) is caused by the bacteria Rickettsia parkeri and Rickettsia rickettsii. Seroepidemiological data on Rickettsia spp. in humans are rare in Brazil and nonexistent in the Amazon biome. We sought to quantify antibodies reactive to Rickettsia spp. in serum samples collected from humans in the Amazonia biome, and to detect Rickettsia spp. in ticks parasitizing these hosts. Methods Human blood samples were collected from three different locations within the eastern Amazon in Maranhão State, northeastern Brazil between 2010 and 2018. Sera generated from those samples were tested for the presence of antibodies reactive to Rickettsia by immunofluorescence assay (IFA) using crude antigens from five Rickettsia isolates from Brazil: R. rickettsii strain Taiaçu, R. amblyommatis strain Ac37, Rickettsia rhipicephali strain HJ5, R. parkeri strain At24, and Rickettsia bellii strain Mogi. Between 2020 and 2025, ticks were manually collected while attached to the skin of humans in seven municipalities in Maranhão State. Adult ticks were randomly selected and individually processed for DNA extraction and examined using a real-time PCR (qPCR) assay targeting a fragment of the rickettsial gltA gene. The qPCR-positive samples were subsequently examined by conventional PCR (cPCR) targeting the ompA gene of SFG rickettsiae. The cPCR amplicons were purified and sequenced bidirectionally using the amplification primers. The resulting sequences were compared with those in GenBank using BLASTn to identify related Rickettsia spp. Results A total of 341 human serum samples were analyzed, and 145 (42.5%) were recorded as reactive with at least one species of Rickettsia. Among the reactive samples, 68 (47%) were from Imperatriz, 45 (31%) from Açailândia, and 32 (22%) from the municipality of São Luís. Rickettsia rhipicephali was recorded as the possible antigen involved in a homologous reaction (PAIHR) in one individual, R. amblyommatis in five, and R. bellii in three. A total of 187 ticks were collected parasitizing humans in the Amazon biome. Molecular analyses revealed that Rickettsia DNA was present in 44.4% (4/9) of A. cajennense s.s. from Açailândia, 52.4% (22/42) from Centro Novo do Maranhão, and 0% (0/8) from Imperatriz. Among the adults of A. coelebs from Centro Novo do Maranhão, 36.8% (7/19) tested positive. In contrast, all adults of A. oblongoguttatum from the same location tested negative (0/20). Conclusions This is the first study to detect anti-Rickettsia antibodies in humans and to identify R. amblyommatis in ticks parasitizing humans in the Amazon biome. The detection of R. amblyommatis in human-biting ticks, together with concurrent seropositivity in human sera from the same region, supports the hypothesis that this agent is actively circulating in the Amazon biome and may be responsible for undiagnosed cases of nonlethal spotted fever in the area. Graphical abstract